The clinical significance of the calf circumference in non‐small‐cell lung cancer patients who undergo surgery - Akihiro Nagoya; Ryu Kanzaki; Kenji Kimura; Eriko Fukui; Takashi Kanou; Naoko Ose; Soichiro Funaki; Masato Minami; Yasushi Shintani (Wiley, 2022)
Abstract Background Calf circumference (CC), the greatest girth of the lower leg, is a simple tool for assessing sarcopenia. Its significance in patients with resectable non‐small‐cell lung cancer (NSCLC) is unknown. Methods A total of 684 NSCLC patients who underwent surgery were included in the present study. The relationship between parameters of sarcopenia [i.e. the CC and skeletal mass index (SMI)] and the short‐term and long‐term outcomes was retrospectively analysed. Results The median CC (34.5 cm for men and 32.0 cm for women) was selected as the cut‐off value of the CC for the analysis in this study, and the patients were classified into the smaller CC (SC) and normal CC (NC) groups. The mean age of the SC group was significantly older than that of the NC group (70.8 vs. 65.8 years, P < 0.01), whereas the body mass index of the SC group was lower than that of the NC group (20.6 vs. 23.6, P < 0.01). The respiratory function of the SC group was poorer in comparison with the NC group. The mean SMI of the SC group was significantly lower than that of the NC group in both men (47.9 vs. 54.1, P < 0.01) and women (40.1 vs. 44.0, P < 0.01). The prevalence of sarcopenia (defined by a lower SMI) was higher in the SC group than in the NC group (38.8% vs. 11.8%, P < 0.01). The post‐operative complication rate was higher in the SC group than in the NC group (28.8% vs. 19.3%, P < 0.01). In the multivariate analysis, the CC was an independent risk factor for grade ≥3 post‐operative complications [odds ratio: 1.90 (1.07-3.38), P = 0.03]. In all patients, the 5 year overall survival (OS) rate of the SC group was significantly worse than that of the NC group (75.5% vs. 82.3%, P < 0.01). The difference in OS according to CC was significant in men but not in women. In a multivariate analysis, the CC was not an independent prognostic factor for the OS [hazard ratio: 1.07 (0.75-1.55), P = 0.70]. When patients were divided into four groups according to the CC and SMI, the CC was able to stratify the OS of patients with a normal SMI (P = 0.02) in men but not in women. Conclusions The CC was found to be a useful predictor for both short‐term and long‐term outcomes. The CC plays a complementary role to the SMI, proving useful for prognostic stratification that was unable to be performed by SMI alone in men.